Bronchodilator response to albuterol nebulized with hypertonic saline in asthmatic children. Issue 12 (9th September 2021) - Teper, Alejandro; Kofman, Carlos; Alchundia Moreira, Jessica; Köhler, Teresa; García Bournissen, Facundo
Abstract: Introduction: Asthma is distinguished by bronchial obstruction reversible by bronchodilators. The first‐line treatment for asthmatic exacerbations is the use of inhaled beta‐agonists, by pressurized metered‐dose inhalers or nebulized with normal saline solution (NSS). There are no reports of nebulized beta agonists' efficacy in asthmatic children when administered with hypertonic saline solution (HSS). Objective: To evaluate bronchodilator responses (BDR) to albuterol nebulized with 3%‐HSS in asthmatic children, compared to albuterol nebulized with NSS. Population and Methods: In a prospective, experimental, double‐blind, randomized clinical study, children with a confirmed diagnosis of asthma with mild or moderate bronchial obstruction (FEV1 40%–79% of predicted) were randomized to receive a nebulization with 2.5 mg of albuterol diluted in 3 cc of 3%‐HSS or NSS (0.9%), by means of a jet nebulizer. After 30 min, the BDR was assessed. Results: Fifty patients (mean age 12.0 ± 3 years, 29 males) were enrolled; 25 were randomized to the 3%‐HSS group (FEV1 65.2% ± 10) and 25 to the NSS group (FEV1 69.1% ± 7.1). The BDR of FEV1 was 41.2% ( SD : ±20.1; 95% confidence interval [CI]: 35.1–50.4) and 17.3% ( SD : ±19.4; 95% CI: 9.7–24.9) ( p < .0001) and of maximum mid‐expiratory flow was 130% ( SD : ±90.8; 95% CI: 94.6–166) and 69.8% ( SD : ±72.5; 95% CI: 41.4–98.2) ( p < .01), for the 3%‐HSS and NSS groups, respectively. Conclusion: Albuterol produces a greater BDR when nebulized with 3%‐HSS compared to NSS in asthmatic children with mild or moderate bronchial obstruction.